SiC Devices for Renewable and High Performance Power Conversion Applications. (26th March 2012) - Abuishmais, Ibrahim; Undeland, Tore M.
Abstract : The unique properties of SiC devices enable substantial improvement of existing power conversion systems. SiC devices offer lower conduction and switching losses which increases converter efficiency. With high switching speed ability, employing SiC is expected to reduce weight and cost of conversion systems. This paper investigates the potential impact of SiC devices on renewable energy applications.